The effect of an after school intervention program on selected health-related physical fitness components among secondary school boys - Raju, S.; Rengasamy, S.; Sia Seng Lee, W.A.; Varatharajoo, C.; Sukumaran, S.D. (2014)
The aim of the study was to investigate the effect of an after school intervention program on selected health-related physical fitness components among Malaysian secondary school boys. A quasi experimental design was adopted for the study. A school in a district was randomly selected. In the school, two classes were randomly assigned intact to the experimental group (n=25) and the other was the control group (n=25). Pretest data was collected on cardiovascular endurance, flexibility and muscular strength. The experimental and the control groups underwent 80 minutes’ regular physical education classes once a week for ten weeks. Apart from the regular physical education classes, the experimental group underwent the intervention program in the form of football training after the school session once a week. After ten weeks, post test data was collected. ANCOVA indicated that there was a main effect in cardiovascular endurance F (1,47) = 62.52, p<.05 and flexibility F (1,47) = 14.18, p<.05. As for muscular strength, the result was not significant F (1,47) = 2.41, p>.05 for the right hand and F (1,47) = 1.63, p>.05 for the left hand. The results indicated that an after school intervention program in the form of football training was effective in enhancing cardiovascular endurance and flexibility among Malaysian secondary school boys.